Is Islam Compatible With Democracy? Islamist Movement’s Trajectory on Democratization in Indonesia - Ahyar, Muzayyin (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
The democratization process in Indonesia is in line with the emergence several Islamic mass organizations which accept or rejected the concept of democracy. Since the pre-independence era, Indonesia has been facing some Islamist groups that opposed to state’s ideology of democracy. This article presents the discussion among scholars about the compatibility between Islamic norms and democratic values, and in what position Indonesia is. The dealing question with the discussion is; does the proliferation of radical Islamist movement signify the incompatibility of Islam and democracy? By using sociological and historical approach, this paper analyzes in order to what extent the values of democracy and Islamism adapt in the frame of a democratic country. The analysis of this research results that the existing radical Islamist movement is not a failure of Indonesia’s effort to harmonize Islam with democracy. Thus, neither the presence of pro-democracy Islamic mass organizations nor the radical Islamist movement cannot be used as the final argument to answer whether Islam compatible with democracy or not. The results of this study reveal that democratization in Indonesia has been accompanied by the proliferation of Islamist movements. The proliferation of Islamist movements nowadays precisely indicates that democracy in Indonesia has a special experience regarding new formula of peacefully religion-state relations.Proses demokratisasi di Indonesia berjalan seiring lahirnya berbagai organisasi masyarakat Islam yang mendukung maupun menolak demokrasi. Sejak era pra-kemerdekaan hingga era reformasi, Indonesia terus dihadapkan dengan fenomena gerakan Isalmisme yang bersebrangan dengan ideologi Negara. Artikel ini menghadirkan diskusi yang selama ini masih banyak didiskusikan mengenai kesesuaian Islam dan demokrasi, dan di mana posisi Indonesia dalam hal kesesuaian dan ketidaksesuaian Islam dan demokrasi tersebut. Pertanyaan kunci dari artikel ini apakah proliferasi gerakan Islamis radikal menandakan ketidaksesuaian Islam dan demokrasi? Dengan menggunakan pendekatan sosiologi dan historis, artikel ini menganalisis sejauh mana nilai-nilai demokrasi dan Islamisme beradaptasi dalam bingkai Negara yang demokratis. Hasil analisis dari kajian ini menemukan bahwa eksistensi gerakan Islamis radikal bukan sebuah pertanda akan kegagalan usaha keras Indonesia dalam mengharmonisasikan Islam dan demokrasi. Sehingga, kehadiran ormas Islam, baik pendukung maupun penolak demokrasi, keduanya tidak dapat dijadikan jawaban final bahwa Islam sesuai atau tidak dengan demokrasi. Hasil dari kajian ini menekankan bahwa demokratisasi di Indonesia selalu diwarnai dengan proliferasi gerakan Islamis. Proliferasi gerakan Islamis akhir-akhir ini justru membuktikan bahwa demokrasi di Indonesia memiliki pengalaman khusus terkait formula hubungan agama-negara dalam masyarakat yang demokratis.